In the Lena Delta : a narrative of the search for Lieut.-Commander DeLong and his companions followed by an account of the Greely Relief Expedition and a proposed method of reaching the North Pole - Melville, George W. (George Wallace), 1841-1912.; Philips, M. (Melville) (Boston : Houghton, Mifflin and Co., 1892)
Mode of access: Internet.